D-dimer levels and 90-day outcome in patients with acute pulmonary embolism with or without cancer - Maestre, Ana; Trujillo-Santos, Javier; Visoná, Adriana; Lobo, José Luís; Grau, Enric; Malý, Radovan; Duce, Rita; Monreal, Manuel; RIETE Investigators (Thrombosis research, 2014)
BACKGROUND: The prognostic value of D-dimer testing in patients with acute pulmonary embolism (PE) has not been thoroughly studied. METHODS: We used the RIETE Registry data to assess the 90-day prognostic value of increased IL Test D-dimer levels at baseline in patients with PE, according to the presence or absence of cancer. RESULTS: As of May 2013, 3,283 patients with acute PE underwent D-dimer testing using IL Test D-dimer. Among 2,588 patients without cancer, those with D-dimer levels in the highest quartile had a higher rate of fatal PE (2.6% vs. 0.9%; p=0.002), fatal bleeding (1.1% vs. 0.3%; p=0.017) and all-cause death (9.1% vs. 4.4%; p<0.001) at 90 days compared with those with levels in the lowest quartiles. Among 695 patients with cancer, those with levels in the highest quartile had a similar rate of fatal PE or fatal bleeding but higher mortality (35% vs. 24%; p<0.01). On multivariate analysis, non-cancer patients with D-dimer levels in the highest quartile had an increased risk for fatal PE (odds ratio [OR]: 3.3; 95% CI: 1.6-6.6), fatal bleeding (OR: 4.3; 95% CI: 1.4-13.7) and all-cause death (OR: 2.1; 95% CI: 1.4-3.1) compared with patients with levels in the lowest quartiles. CONCLUSIONS: Non-cancer patients with acute PE and IL Test D-dimer levels in the highest quartile had an independently higher risk for fatal PE, fatal bleeding and all-cause death at 90 days than those with levels in the lowest quartiles. In patients with cancer, D-dimer levels failed to predict fatal PE or fatal bleeding.
Keywords: Male; Neoplasms; Risk Factors; antikoagulancia; Pulmonary Embolism; Fibrin Fibrinogen Degradation Products; prognóza; Aged; mužské pohlaví; senioři; lidé; ženské pohlaví; Anticoagulants; Humans; rizikové faktory; Prognosis; nádory; Female; plicní embolie; fibrin-fibrinogen - produkty degradace